2011
DOI: 10.1021/bc200289n
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy for Microsphere-Mediated DNA Transfection

Abstract: A new approach for microsphere-mediated delivery of plasmid DNA has been developed and successfully evaluated. Basic molecular biology techniques were used to linearize and functionalize plasmid DNA by aminomodification, enabling efficient conjugation to carboxy-functionalized microspheres. A T cell hybridoma line was successfully transfected as determined by the efficient expression of a biologically relevant YFP fusion protein. Moreover, our data identified microsphere-mediated delivery of plasmid DNA as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Specifically surface-modified polystyrene nanoparticles are homogeneous, exhibit a low polydispersity index, and form stable colloids in biological fluids. These nanodevices have been extensively used as systems for in vitro applications [7][8][9]. Furthermore, these NPs enable solid phase multistep chemistries to become compatible with different bio-orthogonal strategies [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically surface-modified polystyrene nanoparticles are homogeneous, exhibit a low polydispersity index, and form stable colloids in biological fluids. These nanodevices have been extensively used as systems for in vitro applications [7][8][9]. Furthermore, these NPs enable solid phase multistep chemistries to become compatible with different bio-orthogonal strategies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these NPs enable solid phase multistep chemistries to become compatible with different bio-orthogonal strategies [10,11]. Easy entry in a broad range of cell types including adherent, suspensions and primary cell lines has been reported [8][9][10][11][12]. On the other hand, gene-expression profiling studies showed that these NPs did not induce any significant alteration in nanofected cell transcriptomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide linkers have been used effectively in the delivery of nucleic acids to cells (27, 30) and in releasing protein from nanocapsules (31). Such linkers permit intracellular release from a carrier because the cytoplasm of mammalian cells is maintained as a reducing environment, containing high concentrations of reduced glutathione (tripeptide γ-glutamyl-cysteinyl-glycine), which cleaves disulfide bonds to generate free thiols.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the recent demonstrations that polystyrene microspheres can carry a variety of molecular cargoes with them into the cytoplasm (4, 5, 7, 26, 27) make them particularly exciting as potential vectors for delivering functional proteins and/or protein complexes. β-Galactosidase retains its activity when delivered via this route (7), confirming the potential of microspheres to act as generic protein-delivery vehicles.…”
mentioning
confidence: 99%
“…Cellular processes then transported the pDNA to the nucleus resulting in the expression of the protein. [22] Another approach would be the delivery of synthetic siRNA into cells which has increasing applications due to the ability to switch off a genes without the necessity of being transported into the nucleus. [23] Microspheres functionalized with a double stranded siRNA were shown to efficiently silence green fluorescent protein (eGFP) expressed in human cervical cancer (HeLa) cells.…”
Section: The Use Of Microspheres As a Delivery Vectormentioning
confidence: 99%